Biotransformation of penicillin V to 6-aminopenicillanic acid using immobilized whole cells of E. coli expressing a highly active penicillin V acylase - Avinash, Vellore Sunder; Chauhan, Palna Dinesh; Gaikwad, Shraddha; Pundle, Archana (Preparative Biochemistry & Biotechnology, 2017)
The production of 6-aminopenicillanic acid (6-APA) is a key step in the manufacture of semisynthetic antibiotics in the pharmaceutical industry. The penicillin G acylase from Escherichia coli has long been utilized for this purpose. However, the use of penicillin V acylases (PVA) presents some advantages including better stability and higher conversion rates. The industrial application of PVAs has so far been limited due to the nonavailability of suitable bacterial strains and cost issues. In this study, whole-cell immobilization of a recombinant PVA enzyme from Pectobacterium atrosepticum expressed in E. coli was performed. Membrane permeabilization with detergent was used to enhance the cell-bound PVA activity, and the cells were encapsulated in calcium alginate beads and cross-linked with glutaraldehyde. Optimization of parameters for the biotransformation by immobilized cells showed that full conversion of pen V to 6-APA could be achieved within 1 hr at pH 5.0 and 35 degrees C, till 4% (w/v) concentration of the substrate. The beads could be stored for 28 days at 4 degrees C with minimal loss in activity and were reusable up to 10 cycles with 1-hr hardening in CaCl2 between each cycle. The high enzyme productivity of the PVA enzyme system makes a promising case for its application for 6-APA production in the industry.